1999
DOI: 10.1002/(sici)1096-8628(19990507)84:1<61::aid-ajmg12>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The Meier-Gorlin syndrome, or ear-patella-short stature syndrome, in sibs

Abstract: The Meier-Gorlin syndrome, first described by Meier and Rothschild [1959: Helv Paediatr Acta 14:213-216] and further delineated by Gorlin et al. [1975: A Selected Miscellany, p 39-50], is characterized by short stature, slender body build, craniofacial anomalies, microtia, delayed skeletal development, hypogonadism, and absence of the patellae. It has also been called the ear-patella-short stature syndrome [Boles et al., 1994: Clin Dysmorphol 3:207-214]. We report on two brothers with Meier-Gorlin syndrome, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Sixty‐three cases of MGS have been described in literature, thus far [Meier et al, 1959; Gorlin et al, 1975; Hurst et al, 1988; Cohen et al, 1991; Boles et al, 1994; Lacombe et al, 1994; Buebel et al, 1996; Fryns, 1998; Loeys et al, 1999; Verhallen et al, 1999; Terhal et al, 2000; Bongers et al, 2001; Cohen et al, 2002; Feingold, 2002; Shalev and Hall, 2003; Dudkiewicz and Tanzer, 2004; Faqeih et al, 2005; Gezdirici et al, 2010; Guernsey et al, 2011; Bicknell et al, 2011a, b; de Munnik et al, 2012]. Recently, mutations in five different pre‐replication complex genes ( ORC1 , ORC4 , ORC6 , CDT1 , and CDC6 ) were identified in 67% (31/46) of patients with MGS described in literature [Bicknell et al, 2011a, b; Guernsey et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty‐three cases of MGS have been described in literature, thus far [Meier et al, 1959; Gorlin et al, 1975; Hurst et al, 1988; Cohen et al, 1991; Boles et al, 1994; Lacombe et al, 1994; Buebel et al, 1996; Fryns, 1998; Loeys et al, 1999; Verhallen et al, 1999; Terhal et al, 2000; Bongers et al, 2001; Cohen et al, 2002; Feingold, 2002; Shalev and Hall, 2003; Dudkiewicz and Tanzer, 2004; Faqeih et al, 2005; Gezdirici et al, 2010; Guernsey et al, 2011; Bicknell et al, 2011a, b; de Munnik et al, 2012]. Recently, mutations in five different pre‐replication complex genes ( ORC1 , ORC4 , ORC6 , CDT1 , and CDC6 ) were identified in 67% (31/46) of patients with MGS described in literature [Bicknell et al, 2011a, b; Guernsey et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Only one patient was reported to have normal sized and shaped ears [Bicknell et al, 2011b]. Additionally, genital growth may be specifically affected both evident at birth, resulting in minor genital anomalies, and during secondary sexual development, resulting in mammary hypoplasia [Gorlin et al, 1975; Lacombe et al, 1994; Buebel et al, 1996; Loeys et al, 1999; Terhal et al, 2000; Bongers et al, 2001; Shalev and Hall, 2003; Guernsey et al, 2011; Bicknell et al, 2011a].…”
Section: Introductionmentioning
confidence: 99%
“…Ear-patella-short stature syndrome (MGS) has become one of the increasingly recognized disorders and to date, at least cases of 35 patients have been published [Meier et al, 1959;Gorlin et al, 1975;Hurst et al, 1988;Cohen et al, 1991;Boles et al, 1994;Lacombe et al, 1994;Buebel et al, 1996;Teebi and Gorlin, 1997;Fryns, 1998;Loeys et al, 1999;Verhallen et al, 1999;Terhal et al, 2000;Bongers et al, 2001;Cohen et al, 2002;Feingold, 2002;Shalev and Hall, 2003;Dudkiewicz and Tanzer, 2004]. We observed a new patient with a previously unrecognized finding.…”
Section: To the Editormentioning
confidence: 69%
“…Few studies have documented variable results of endocrine work-up, including growth hormone assays. Loeys et al [1999] reported two brothers with MGS, delayed bone age, one of whom was subjected to glucagon stimulation test with subnormal GH and borderline Somatomedin C. Cohen et al [2002] reported on an 18.5-year-old patient that had severe proportionate short stature, and received recombinant GH therapy, though he has normal GH assay. They concluded that short stature was probably not related to growth hormone deficiency.…”
Section: To the Editormentioning
confidence: 99%
“…In some of the previously reported patients, environmental factors were believed to be associated with the developmental delay. For example, Loeys et al [1999] reported two brothers who were considered to have retardation but after a program of “intensive psychosocial stimulation,” they showed remarkable progress. It would be worthwhile to re‐evaluate the other patients who were considered to have mental retardation to make certain the delays were not due to social or other environmental factors.…”
Section: To the Editormentioning
confidence: 99%